Prostate cancer awareness and attitude toward early detection among male soldiers in Ghana: a cross‑sectional study - Anaba, E.A.; Necku, J.G.; Abuosi, A.A. (African Journal of Urology, 2019)
Background: Prostate cancer (PC) is the leading cause of cancer deaths among men in Ghana. This poses a public health threat, especially among the Ghana Armed Force (GAF) where the majority are males. This study aimed to assess male soldiers’ awareness, knowledge and attitudes toward early detection of prostate cancer. Results: It was found that 58.3% of the soldiers were less aware of PC and 76.0% had low or neutral knowledge regarding risk factors and symptoms of PC. The soldiers had positive attitudes toward early detection but had low intentions of getting tested. Awareness was significantly associated with education, rank, haven received PC information from a health worker and being knowledgeable of signs of PC. Conclusion: We recommend that management of the GAF should liaise with the Ministry of Health to sensitize and educate soldiers on prostate cancer, and if possible, organize periodic screening activities for the soldiers to aid in early detection and effective management of the disease. The findings of this study provide valuable information for health interventions in Ghana.
Research Article
Keywords: Prostate; Cancer; Knowledge; Attitudes; Ghana